Optimizing health-related quality of life assessments for stroke survivors: a validation study of psychometric properties for the Vietnamese version of stroke impact scale 3.0 - Nguyen, Thao Thi Phuong; Hoang, Hai Bui; Vu, Huyen Thi Thanh; Lee, Seung Won (Frontiers in Public Health, 2025)
BackgroundEnsuring lifelong health among aging populations necessitates comprehensive assessments of functional recovery and quality of life, particularly for vulnerable groups such as older adult stroke survivors. While the Stroke Impact Scale (SIS) 3.0 is a widely validated instrument for evaluating health-related quality of life (HRQoL) in stroke survivors, its psychometric properties have not yet been examined in the Vietnamese context. This study aimed to translate, culturally adapt, and validate the Vietnamese version of the SIS 3.0 (V-SIS 3.0), providing a robust tool to support holistic, multidimensional approaches to stroke rehabilitation in aging populations.MethodsA cross-sectional study was conducted from July to December 2021 at the National Geriatric Hospital in Hanoi, Vietnam. The study enrolled 256 stroke survivors aged 45 years or older who had experienced a stroke between 1 month and 1 year prior to participation. The V-SIS 3.0 questionnaire was developed through a rigorous forward and backward translation process. Its factorial structure was examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Internal consistency was assessed via Cronbach’s alpha, and convergent and divergent validity were evaluated through correlation analyses. Additionally, Item Response Theory (IRT) was employed to examine item discrimination and difficulty.ResultsEFA identified a four-factor structure consisting of Physical (28 items), Cognitive (12 items), Social Participation (10 items), and Emotional (8 items) domains. CFA supported this structure, indicating a good model fit (RMSEA = 0.080, CFI = 0.925, TLI = 0.918, SRMR = 0.053). The instrument demonstrated excellent internal consistency across all domains, with Cronbach’s alpha values of 0.971 for Physical, 0.950 for Cognitive, 0.949 for Social Participation, and 0.920 for Emotional. Convergent and divergent validity were confirmed by strong item correlations within each factor, while IRT analysis further indicated high discrimination and appropriate difficulty levels for most items.ConclusionThe V-SIS 3.0 is the first culturally adapted and validated tool to assess HRQoL in Vietnamese stroke survivors. By offering a reliable, multidimensional evaluation of physical, cognitive, emotional, and social wellbeing, this instrument enhances clinical assessments, informs targeted interventions, and ultimately contributes to more effective aging and lifestyle strategies for stroke survivors in Vietnam.